Tingkat Akurasi Servis Forehand Backspin - Haryanto, Jeki; Murniati, Murniati; Sari, Dessi Novita (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2021)
The purpose of this study was to determine the level of accuracy of forehand backspin service in PTM Punggung Kasiak, so that the results are expected to be used as a reference to improve or maintain the quality of athlete service accuracy at the club or in other clubs. Service is very useful as a main weapon in a match that is very closely related to the player's strategy to be applied to face opponents. This type of research uses the type of quantitative descriptive research in which the researcher only seeks to dig up information about the accuracy of the forehand backspin serve. The sampling technique used in this study is census sampling, which means that the entire population is used as a sample, while the data collection is done by directly conducting tests on 13 early childhood athletes at Punggung Kasiak Table Tennis Club in Padang Pariaman, West Sumatra. The data obtained were analyzed using descriptive statistical techniques. The results showed that the average level of accuracy of the forehand backspin serve in early childhood athletes in this club is in the category of moderate, which mean they have standart service accuracy that should be improve for their future career in table tennis.